Schweizer-Sklar power aggregation operators based on complexsingle-valued neutrosophic information using SMART and their application in green supply chain management - Priyadharshini S; Mohanaselvi S (Neutrosophic Sets and Systems)
A complex single-valued neutrosophic (CSVN) set is a very useful tool to handle the uncertainty, inconsistency, and ambiguity of knowledge in a periodic framework. The Schweizer-Sklar (SS) t-norm (TN) and t-conorm (TCN) enhance the flexibility of a procedure for aggregation depending on its parameters, whereas the power aggregation(PA) operator prevents insufficient impact of excessively high or low arguments on the results. Based on the idea of Schweizer-Sklar power aggregation operators, this paper aims to propose a number of aggregation operators such as complex single-valued neutrosophic Schweizer-Sklar power weighted averaging (CSVNSSPWA), complex single-valued neutrosophic Schweizer-Sklar power ordered weighted averaging (CSVNSSPOWA). Weights determination to solve green supply chain management problems in the single valued neutrosophic context is accomplished through the Simple Multi-Attribute Rating Technique (SMART). Furthermore, an example is given to show the uniqueness of the proposed operator and the difference between the proposed work and previous research.